Patterns of Social Media Usage among Malaysians During the Covid-19 Pandemic - Aisah Meri; Syahruddin Awang Ahmad; Sitinurbayu Mohd Yusoff; Noor Syakirah Zakaria; Fauzie Sarjono; Amrullah Maraining; Zainuddin Baco (Conscientia Beam, 2022)
This paper explores the use of social media among Malaysians during the Covid-19 pandemic. Questionnaires were distributed to 424 people in Malaysia who were directly affected by the Covid-19 pandemic. The research findings revealed that the main reasons that drove people to use social media were cognitive aspects, escapism, affective factors, and social integration. The data also shows that Malaysians frequently employed social media to search for information, for diversion purposes, and due to habit. Meanwhile, the highest levels of gratifications were derived from factors of convenience, surveillance, and interpersonal discussion. This study concludes that social media plays a crucial role for Malaysians while confronting the Covid-19 pandemic, alongside other media components. It cannot be denied that technology also influenced uses and gratifications among the audiences. The uniqueness of social media, coupled with the smartphone, gives it a distinct advantage over other media forms. The audiences had at their disposal a multitude of information that could bring numerous usages and forms of gratifications.